90 Rapid exome sequencing service for acutely unwell children with a likely monogenic disorder. (30th November 2020) - Steel, Edward; Leitch, Harry; Cobben, Jan; Wakeling, Emma
Abstract : The Rapid exome sequencing service for acutely unwell children with a likely monogenic disorder was launched by NHS England in October 2019. The aim of this new service is to facilitate the rapid diagnosis of genetic conditions in paediatric patients in intensive care settings where a single gene disorder is likely and diagnosis is expected to result in an immediate change in patient management. Funding is provided for recruitment of up to 700 patients per year via seven Genomic Medicine Services (GMS) across England. Trio (patient and both parents) exome sequencing is offered for all referrals accepted by the testing laboratory in Exeter. Patient and parent exomes are compared to identify variants in single genes which may point to a diagnosis. Results are returned to the referring department with a target turnaround time of 21 days. All referrals from clinicians within the region covered by the London North GMS are reviewed by the North East or North West Regional Genetics Services (based at GOSH and Northwick Park Hospital, respectively) to ensure that patients meet eligibility criteria. The service is targeted toward patients in neonatal and paediatric intensive care units (NICU/PICU). However acutely unwell patients in other settings are accepted on a case-by-case basis, as are unwell or deceased patients where there is a time-sensitive risk of recurrence in a current pregnancy. Reasons for rejection include a diagnosis being unlikely to impact management, a likely environmental or polygenic cause, and more specific or appropriate methods of testing being available. We present the uptake and outcomes of the service across the London North region in the first year of recruitment.